Isolation and Antimicrobial Activity Test of n-Hexane of Pineapple Core Ananas comosus L. Merr - Siti Juariah; Rival Juliansyah; Nurlaila Wahyuni (Jurnal Penelitian Pendidikan IPA, 2025)
Pineapple (Ananas comosus L. Merr) contains various bioactive compounds, including the enzyme bromelain. Pineapple pith was chosen as a sample because it is still underutilized. This study aims to isolate secondary metabolite compounds from n-hexane extract of pineapple bark and test its antimicrobial activity. Maceration was carried out using n-hexane solvent, then the extract was separated by gravity column chromatography, resulting in four fractions. Separation of pure compounds using thin layer chromatography (KLT) with n-hexane:ethyl acetate (4:1) eluent. The second fraction produced a white crystalline compound (Ac-EH) with a melting point of 128-130°C. Characterization with UV-Vis showed absorption at λmax 268 nm and 206 nm, while FTIR identified the functional groups C-O (1047 cm-¹), CH₃ (1379 cm-¹), CH₂ (1465 cm-¹), C-H aliphatic (2939 cm-¹), and OH (3309 cm-¹). Phytochemical tests showed that Ac-EH belongs to the terpenoid group. Antimicrobial activity tests against Staphylococcus aureus, Staphylococcus epidermidis, and Candida albicans were carried out by diffusion method at concentrations of 20%, 30%, and 40%. The results showed that the n-hexane and Ac-EH extracts were active in inhibiting bacterial growth but not against fungi. The n-hexane extract inhibited S. aureus by 9.1 mm, 9.5 mm, and 9.8 mm and S. epidermidis by 8.1 mm, 8.4 mm, and 8.7 mm. The Ac-EH compound inhibited S. aureus by 8.5 mm, 8.9 mm, and 9.4 mm and S. epidermidis by 8.3 mm, 8.7 mm, and 9.1 mm.